In vitro Neuroprotective Potential and Lipidomics Study of Olive Leaves Extracts Enriched in Triterpenoids - Gallego, Rocío; Suárez-Montenegro, Zully J.; Ibáñez, Elena; Herrero, Miguel; Valdés, Alberto; Cifuentes, Alejandro (Frontiers in Nutrition, 2021)
Alzheimer's Disease (AD) is the most common form of dementia that is associated with extracellular amyloid beta (Aβ) plaque formation. Genetic, environmental and nutrition factors have been suggested as contributors to oxidative stress and neuroinflammation events that are connected to AD etiology, and secondary metabolites, such as triterpenes, have shown promising results in AD prevention. In this work, the neuroprotective and anti-inflammatory potential of an olive leaves fraction enriched in triterpenoid compounds obtained using supercritical fluid extraction (SFE) and dynamic adsorption/desorption using sea sand as adsorbent has been performed. In addition, a comprehensive lipidomics study of the response of SH-SY5Y neuroblastoma cell line to this fraction was carried out using advanced analytical methodologies, namely, charged-surface hybrid chromatography-quadrupole-time of flight mass spectrometry (CSH-Q-TOF MS/MS). The use of freely available lipidomic annotation tools and databases, and stringent cut-off filters allowed the annotation of more than 250 intracellular lipids. Advanced bioinformatics and statistical tools showed a number of phosphatidylcholines and phosphatidylethanolamines significantly increased, which could explain the protection against the cell death caused by Aβ1-42. Moreover, several triacylglycerols were found decreased. These results suggest triterpenoids from olive leaves as good neuroprotective candidates, and open a new gate for future experiments using in vivo models to corroborate this hypothesis.